SISTEM INFORMASI PENDAFTARAN MITRA GRABCAR PADA PT. GRABCAR INDONESIA (CKI ON SPOT, 2018)
High technological developments have brought many changes to our lives, information technology is perceived to have an important role because with the advancement of information technology will improve the productivity of the industrial world, especially from the field of creative industries based applications. This can be seen by the presence of many online transportation applications in Indonesia. One of them is PT. GRABCAR INDONESIA a brand that is the result of the rebranding of GrabTaxi. The Grab hopes the Jakarta community can become a loyal customer of Grab transportation service. The Grab Company will also take note of the drivers that are available today, can be seen from the customer response where the comparison between passengers and driver partners found there are still long-standing customers. The strategy that has been done by Grab's company has been provided registration online for driver partner Grab. In order to provide satisfied service and good experience when traveling with Grab transportation services. In order for the Grab transport service company to get a positive response from the company community Grab will think about how to make all customers satisfied with Grab transportation services and can be a material improvement for transportation service company Grab.